The Application of Consumer Psychology in Xiaomi’s Marketing Strategy: A 4C Analysis - Zhang, Yajing (Transactions on Social Science, Education and Humanities Research, 2024)
Xiaomi Technology Co., LTD. (referred to as Xiaomi from now on) is a Fortune Global 500 company in the electronic information industry. Studying Xiaomi's marketing strategy can help researchers understand how enterprises win consumers through innovative thinking and marketing means in the digital and internet market, and how to create competitive advantages in the market where products are almost the same. The author investigated Xiaomi’s marketing strategy from the perspective of consumer psychology, and used 4C theory to analyze. The result shows that Xiaomi's success is closely related to the application of consumer psychology in its marketing strategy. Using scarcity, relative advantage and simplicity, Xiaomi meets customers’ needs nicely. And for lower prices, better products and promotions to meet bargain hunting psychology, Xiaomi greatly reduces customers’ costs to boost sales volume. By providing a better buying experience as well as better after-sale service, Xiaomi emphasized the importance of its customer convenience. Lastly, Xiaomi is good at word-of-mouth marketing and creates a brand personality of sincerity in communicating with customers. With a good application of consumer psychology, Xiaomi has developed an effective marketing strategy to meet the needs of consumers and improve their purchase willingness and satisfaction.